Staphylococcus aureus nasal carriage might be associated with vitamin D receptor polymorphisms in type 2 diabetes. (6th March 2014) - Messaritakis, I.; Samonis, G.; Dimopoulou, D.; Maraki, S.; Papadakis, J. A.; Daraki, V.; Fragaki, M.; Choulaki, C.; Andrianaki, A. M.; Kofteridis, D. P.; Lina, G.
Abstract Vitamin D receptor (VDR) gene polymorphisms have been associated with susceptibility to several diseases, including type 1 diabetes (T1D), type 2 diabetes (T2D), and various infections. The study investigated whether VDR gene polymorphisms influence nasal carriage of Staphylococcus aureus in individuals with T2D, an important source for bloodstream, surgical site and other nosocomial infections. In 173 patients with T2D genotyped for the VDR gene polymorphisms on FokI (rs10735810) F>f, BsmI (rs1544410) B>b, ApaI (rs7975232) A>a, and TaqI (rs731236) T>t, a nasal swab was obtained to detect colonization by S. aureus. A repeat swab was obtained in 162/173 subjects for the estimation of persistent S. aureus carriage. The prevalence of S. aureus nasal colonization was 19.7% and of persistent carriage was 8.6%. Nasal colonization by S. aureus was more common in individuals with FokI f allele than F allele (p 0.05; OR 1.69, 95% CI 1.00–2.89) and individuals with FokI ff genotypes were more frequently colonized than those with FokI FF and Ff genotypes combined (p 0.03; OR 2.61, 95% CI 1.14–5.99). The presence of the FokI f allele was related to higher rates of S. aureus persistent nasal colonization (p 0.002; OR 3.53, 95% CI 1.56–7.98), and individuals with a FokI ff genotype were more often persistent carriers than those with FokI FF and Ff genotypes combined (p <0.001; OR 7.32, 95% CI 2.39–22.41). This study is the first, to our knowledge, to show an association between FokI polymorphism in the VDR gene and nasal carriage of S. aureus in individuals with T2D.